2015
DOI: 10.7202/1032504ar
|View full text |Cite
|
Sign up to set email alerts
|

Vote stratégique au Québec : analyse de l’élection de 2012

Abstract: Bien que le vote stratégique soit un thème récurrent lors des campagnes provinciales électorales québécoises, aucune étude n’a analysé le vote stratégique au Québec. En utilisant un sondage du projet Making Electoral Democracy Work, cet article comble cette lacune dans la littérature et analyse l’élection québécoise de 2012 en répondant à deux objectifs principaux : déterminer la proportion de votes stratégiques et identifier les variables individuelles qui influencent la probabilité qu’un électeur opte pour u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
(24 reference statements)
0
6
1
3
Order By: Relevance
“…Indeed, feeling close to a party increases the expressive cost of strategic voting and is thus negatively associated with strategic voting, but that association is not significant. Furthermore, the level of political information is negatively correlated with strategic voting, a finding that differs from other studies, which have found a positive but not significant relationship (Blais and Gschwend 2011;Daoust 2015;Duch and Palmer 2002). Education, however, displays a positive sign, meaning that sophistication but not information might be positively related to strategic voting.…”
Section: The Impact Of Attitudes Toward Minority Government and Coalicontrasting
confidence: 82%
See 1 more Smart Citation
“…Indeed, feeling close to a party increases the expressive cost of strategic voting and is thus negatively associated with strategic voting, but that association is not significant. Furthermore, the level of political information is negatively correlated with strategic voting, a finding that differs from other studies, which have found a positive but not significant relationship (Blais and Gschwend 2011;Daoust 2015;Duch and Palmer 2002). Education, however, displays a positive sign, meaning that sophistication but not information might be positively related to strategic voting.…”
Section: The Impact Of Attitudes Toward Minority Government and Coalicontrasting
confidence: 82%
“…Political sophistication is one of the most studied determinants of strategic voting. Most of the time, the relationship is positive: more sophisticated voters are more likely to vote strategically Merolla and Stephenson 2007), although some authors find null results (Blais and Gschwend 2011;Daoust 2015;Duch and Palmer 2002). Partisanship is also known to impact the proclivity to vote strategically.…”
Section: National Determinants Of Strategic Votingmentioning
confidence: 99%
“…A rich literature examines strategic considerations at the level of the district and evaluates the extent to which voters desert their preferred party when that party has little chance of winning in their constituency. They find that about 3 to 8 per cent of voters strategically desert their preferred party (Blais and Nadeau, 1996; Blais et al, 2001; Daoust, 2015). Others have examined how voters react to local candidates.…”
mentioning
confidence: 99%
“…L'information politique liée à la campagne électorale est mesurée par la connaissance des slogans de campagne adoptés par les principaux partis politiques et par les promesses faites par ces derniers (Zaller, 1991 ;Kwak, 1999 ;Daoust, 2015). Cette mesure est idéale car elle cible l'information propre à une campagne -un individu politisé, même s'il possède une bonne connaissance politique générale, ne pourra pas répondre correctement à ces questions s'il n'a pas été attentif lors de la campagne.…”
Section: Méthodologieunclassified